2023
DOI: 10.3389/fpls.2023.1232804
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and molecular evolution of NAC gene family in Dendrobium nobile

Chun Fu,
MingYu Liu

Abstract: NAC transcription factors are an important genes that regulate plant growth and development, and can regulate functions such as fruit ripening in plants. Based on genome data of Dendrobium nobile, the NAC gene family was identified and analyzed by bioinformatics methods. In this study, we identified 85 NAC genes in Dendrobium nobile genome, and systematically analyzed the NAC gene family. We found that they were distributed unevenly in the nineteen chromosomes. The amino acid length of D. nobile NAC gene famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…There are 28 high-use codons (RSCU>1), 11 of which end in C, 10 of which end in U, 5 of which end in G, and 2 of which end in A. This result implies that the preferences for high-use codons terminate with C, However, low-use codons terminate with A, which is significantly distinct from the results of the NAC gene family in D.nobile (Fu and Liu, 2023). The heatmap clustering of codons RSCU of DnTCP genes revealed that members exhibit similar codon usage biases in same branch (Figure 6).…”
Section: Codon Usage Bias and Relative Synonymous Codon Usage Of Dntc...mentioning
confidence: 71%
See 1 more Smart Citation
“…There are 28 high-use codons (RSCU>1), 11 of which end in C, 10 of which end in U, 5 of which end in G, and 2 of which end in A. This result implies that the preferences for high-use codons terminate with C, However, low-use codons terminate with A, which is significantly distinct from the results of the NAC gene family in D.nobile (Fu and Liu, 2023). The heatmap clustering of codons RSCU of DnTCP genes revealed that members exhibit similar codon usage biases in same branch (Figure 6).…”
Section: Codon Usage Bias and Relative Synonymous Codon Usage Of Dntc...mentioning
confidence: 71%
“…and PlantPAN 4.0 ( http://plantpan.itps.ncku.edu.tw/plantpan4/promoter_analysis.php ). Meanwhile, the essential codon metrics such as effective number of codons (ENc), codon adaptation index/bias index (CAI/CBI), and frequency of optimal codons (Fop) were determined using the CodonW1.4.2 program ( Wang et al., 2022 ; Fu and Liu, 2023 ). A heatmap clustering the relative synonymous codon usage (RSCU) of the TCP gene family in D. nobile was generated by using TBtools.…”
Section: Methodsmentioning
confidence: 99%
“…Through comprehensive analysis using relevant databases and software tools, a recent detailed study on Dendrobium nobile revealed the localization of DnoNACs as follows: 70 members in the nucleus, 6 in the chloroplast (DnoNAC11, DnoNAC12, DnoNAC23, DnoNAC30, DnoNAC69, and DnoNAC80), 3 in the cytoplasm (DnoNAC26, DnoNAC74, and DnoNAC78), 3 in the mitochondria (DnoNAC55, DnoNAC76, and DnoNAC83), and 3 in the peroxisome (DnoNAC16, DnoNAC17, and DnoNAC43) [78]. These locations align with those found for the Passiflora edulis NAC TF family [69].…”
Section: Unraveling the Complex Molecular Nac Structurementioning
confidence: 99%
“…Tumida [166], Liriodendrum [4], Hibiscus hamabo Sieb [167], and other species (see Introduction from [168]). Likewise, accumulated studies have shown that there are currently 117 NAC genes in Arabidopsis [169], 163 in poplar [170], 74 in Vitis vinifera [171], 85 in Liriodendrum [4], 151 in rice [54], 110 in potato [156], 152 in tobacco [172], 152 in soybean [154], 97 in Medicago truncatula [173], 104 in tomato [53], 204 in Chinese cabbage [174], 152 in maize [155], 85 in Dendrobium nobile [78], 150 in Helianthus annus [46], 105 in passion fruit (Passiflora edulis) [69], and 123 in Pinus tabuliformis [60]. Similarly, the genome-wide identification of NAC genes has been extended to numerous plant species (see Introduction and Discussion in [175]).…”
Section: Recent Novelties In Stress Response By Nacs Genesmentioning
confidence: 99%
“…Their numbers are fewer only than those for bHLH, ERF and MYB. For example, 183 PbNAC genes were identified in white pear, 180 in apple, 167 NAC in cassava; 85 in Dendrobium nobile, 90 NAC in Dendrobium catenatum, 152 in Glycine max, 151 in Oryza sativa, and 226 such genes were identified in Triticum aestivum [46][47][48][49][50]. Recent studies have shown that the genes of the NAC family participate widely in various biological processes [51][52][53][54].…”
Section: Identification and Evolution Of Nac Transcription Factorsmentioning
confidence: 99%